Transepithelial transport of nanoparticles in oral drug delivery: From the perspective of surface and holistic property modulation - Yaxian Zheng; Shiqin Luo; Min Xu; Qin He; Jiang Xie; Jiawei Wu; Yuan Huang (Elsevier, 2024)
Despite the promising prospects of nanoparticles in oral drug delivery, the process of oral administration involves a complex transportation pathway that includes cellular uptake, intracellular trafficking, and exocytosis by intestinal epithelial cells, which are necessary steps for nanoparticles to enter the bloodstream and exert therapeutic effects. Current researchers have identified several crucial factors that regulate the interaction between nanoparticles and intestinal epithelial cells, including surface properties such as ligand modification, surface charge, hydrophilicity/hydrophobicity, intestinal protein corona formation, as well as holistic properties like particle size, shape, and rigidity. Understanding these properties is essential for enhancing transepithelial transport efficiency and designing effective oral drug delivery systems. Therefore, this review provides a comprehensive overview of the surface and holistic properties that influence the transepithelial transport of nanoparticles, elucidating the underlying principles governing their impact on transepithelial transport. The review also outlines the chosen of parameters to be considered for the subsequent design of oral drug delivery systems.